Serum uric acid and atrial fibrillation. (17th November 2017) - Manolis, Athanasios J.
Abstract: Background: Atrial fibrillation (AF) represents a significant health concern, due to the increased prevalence, morbidity, and mortality. Methods and Results: There is a growing body of evidence correlating serum uric acid (SUA) with cardiovascular diseases such as arterial hypertension and AF. Conclusion: Thus, a question arises as to whether SUA levels have a role in the pathophysiology of AF development.